Effect of Pipe Wall Wear Defects on the Flow Characteristics of Slurry Shield Discharge Pipe - Yingran Fang; Xinggao Li; Xingchun Li; Yidong Guo; Hongzhi Liu (Lubricants)
During slurry shield tunneling in hard rock or cobble strata, the discharge pipes suffer serve wear and damage. However, the effect mechanism of pipe wall wear defects on the flow characteristics of two-phase flow is unclear. In this study, a three-dimensional slurry particle model of pipeline transport was established using the coupled computational fluid dynamics–discrete element method (CFD-DEM) considering the pipe wall wear defect, and the typical pipeline forms of straight pipe and 90° elbow pipe were selected as the research targets. The results indicated that the localized wear defect of pipes can lead to increased inhomogeneity in the velocity distribution, generating localized low-flow zones and resulting in a reduced flow rate or stagnancy in parts of the pipe. Meanwhile, the wear defect of the pipe results in local shape changes, so that the fluid flow path through the pipe is no longer smooth, causing more vortex/turbulence and secondary flow, where an increased vortex promotes localized kinetic energy reduction and creates larger pressure losses at the elbow. In addition, for the elbow pipe without wear defect, the pressure drop of the elbow increases quadratically from an increase of 6.5% to an increase of 16.9%, with the maximum wear depth increasing from 4 mm to 19 mm. For the straight pipe without wear defect, the pressure drop of the elbow increases linearly, from an increase of 2.2% to an increase of 10.2% with the maximum wear depth increasing from 4 mm to 19 mm. The paper investigates the potential mechanism of pipe flow characteristics influenced by wear defect and provides practical guidelines for the efficient operation of a slurry shield circulating system.